BROWNFIELD SITES AND PROPERTY MARKET SENSITIVITY - Zihannudin, Nur Zafira; Adi Maimun, Nurul Hana; Ibrahim, Nurul Liyana (PLANNING MALAYSIA, 2021)
The existence of Brownfield sites is one of the main challenges that Malaysia must face due to financial, administrative and policy problems. The negative environmental and social impacts of Brownfield sites jeopardise residents’ health and well-being, causing nearby areas to be less desirable for occupation and investment. These impacts result in price discounts. Hence, this research aims to establish the sensitivity of the property market towards Brownfield sites through a critical review. An overview of previous studies shows that property prices are sensitive towards Brownfield sites. This indicates that the proximity to a Brownfield site is considered when making property purchase decisions. Thus, property valuers, planners and developers should consider the Brownfield factor during property planning, development and valuation.